On an Application of Parseval’s Formula to Problems of G_θ^-summability of Eigenfunction Expansion of the Laplacian Operator - Vuković, Mirjana; Ilić-Georgijević, Emil; Stevanović, Olivera (Sarajevo Journal of Mathematics, 2024)
To the memory of deeply respected Academician Mahmut Bajraktarević In this paper, applying Parseval's formula, we prove a G_θ^–summability analogue of Avadhani's theorem for the Riesz–summability of the eigenfunction expansion. A crucial step in our proof of this theorem was to find a function g(x) that would lead us to the kernel of the G_θ^–summability, which is more complex than the kernel of the Riesz – summability.